AN ANALLYSIS OF STUDENTSâ ERRORS IN ENGLISH NEGATION AT THE 2nd SEMESTER OF THE 7th CLASS OF SMP PGRI 3 BANDAR LAMPUNG - Damiri, Adenan (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2012)
In teaching and learning English as a foreign language. The students should have the ability in using it in speaking or writing. However to be ableto speak or write well, the students should have the mastery of structure. Because if they have lack of structure they will make errors. It is therefore, the writer would like to analyze the studentsâ errors in using English negation.The subject is the students at the second semester of the seventh class of SMP PGRI 3 Bandar that consists of 40 students. In the data collecting technique the writer used essay test writing test, it means that ask the students to answer based on the teacherâ questions in written dialogue and in analyzing the data the students was used surface strategy taxonomy.Based on the data analyzing of studentsâ English negation of their writing dialogue, the writer described that there are 25 students who madeerrors from 40 students= 62.5%. And from 40 students the writer found 440 sentences. From 440 students, there are 199 in correct sentences= 27.04%.. From 199 incorrect sentence or errors, there are 16 sentences in omission errors= 13.45%; addition errors is 16 sentences= 13.45%;misformation errors is 81 sentences = 68.06%; and misordering errors is 6 sentences= 5.04%. Based on kind of errors, it can be seen that misformation is the highest errors and misordering errors is lowest error.Most of the studentsâ errors because of the studentsâ ability of structure. It means that the students have lack of structure mastery especiallyin using auxiliary verb and the using of ânotâ and also the using tenses.